Pomalidomide mitigates neuronal loss, neuroinflammation, and behavioral impairments induced by traumatic brain injury in rat. Issue 1 (December 2016) - Wang, Jing-Ya; Huang, Ya-Ni; Chiu, Chong-Chi; Tweedie, David; Luo, Weiming; Pick, Chaim; Chou, Szu-Yi; Luo, Yu; Hoffer, Barry; Greig, Nigel; Wang, Jia-Yi
Abstract Background Traumatic brain injury (TBI) is a global health concern that typically causes emotional disturbances and cognitive dysfunction. Secondary pathologies following TBI may be associated with chronic neurodegenerative disorders and an enhanced likelihood of developing dementia-like disease in later life. There are currently no approved drugs for mitigating the acute or chronic effects of TBI. Methods The effects of the drug pomalidomide (Pom), an FDA-approved immunomodulatory agent, were evaluated in a rat model of moderate to severe TBI induced by controlled cortical impact. Post-TBI intravenous administration of Pom (0.5 mg/kg at 5 or 7 h and 0.1 mg/kg at 5 h) was evaluated on functional and histological measures that included motor function, fine more coordination, somatosensory function, lesion volume, cortical neurodegeneration, neuronal apoptosis, and the induction of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6). Results Pom 0.5 mg/kg administration at 5 h, but not at 7 h post-TBI, significantly mitigated the TBI-induced injury volume and functional impairments, neurodegeneration, neuronal apoptosis, and cytokine mRNA and protein induction. To evaluate underlying mechanisms, the actions of Pom on neuronal survival, microglial activation, and the induction of TNF-α were assessed in mixed cortical cultures following a glutamate challenge. Pom dose-dependently ameliorated glutamate-mediated cytotoxic effects on cell viability and reduced microglial cell activation, significantly attenuating the induction of TNF-α. Conclusions Post-injury treatment with a single Pom dose within 5 h significantly reduced functional impairments in a well-characterized animal model of TBI. Pom decreased the injury lesion volume, augmented neuronal survival, and provided anti-inflammatory properties. These findings strongly support the further evaluation and optimization of Pom for potential use in clinical TBI.